2016
DOI: 10.1615/critreveukaryotgeneexpr.2016016683
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer Activities of Medicinal Plants: Modulation of p53 Expression and Induction of Apoptosis

Abstract: For the treatment of several types of cancers, tumors and malignancies, scientists are investigating natural sources to discover novel therapeutic agents from medicinal plants having diverse anticancer properties. Research on natural products is being conducted to identify unexplored phytochemical constituents that have been proven to have diverse pharmacological activities. Several medicinal plants have been reported to regulate the progression of different types of cancers, tumors, and malignancies. In this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…This review also reveals the importance of natural products or their derivatives in cancer suppression or inhibition as a cheap and easily accessible source with a low number of side effects [13,14,15,16] as detailed in Figure 6. The combined use of synthetic drugs as chemotherapy, such as anti-metabolites, antibiotics, alkylating agents, microtubules inhibitors, monoclonal antibodies, and steroid hormones and their antagonists, causes patients to suffer from unbearable side effects, including resistance, multidrug resistance, toxicity, and treatment-induced tumor [144,145].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This review also reveals the importance of natural products or their derivatives in cancer suppression or inhibition as a cheap and easily accessible source with a low number of side effects [13,14,15,16] as detailed in Figure 6. The combined use of synthetic drugs as chemotherapy, such as anti-metabolites, antibiotics, alkylating agents, microtubules inhibitors, monoclonal antibodies, and steroid hormones and their antagonists, causes patients to suffer from unbearable side effects, including resistance, multidrug resistance, toxicity, and treatment-induced tumor [144,145].…”
Section: Discussionmentioning
confidence: 99%
“…through machine learning methods could also be a novel source of potential agents [9,10,11,12]. Interestingly, extracts of natural products or their derived phytochemicals can target and attack several cancer-causing factors, and they are more effective, cheaper, easy to access, and have a low number of side effects, thereby enhancing patient compliance and ultimately being beneficial to achieve a healthy and happy life [13,14,15,16]. This review aims to understand the mechanism underlying VEGF interaction with cancer-causing factors and how they are interlinked with the bioactive constituents that have recently been identified and derived from natural products to inhibit cancer development and metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, the predicted distribution of Selaginella plana's suitable habitat has almost the same pattern as the predicted suitable habitat for S. ciliaris. Several documents and studies had also reported the occurrence of S. plana in Vietnam (Spring 1843;Chang et al 2012), Cambodia (Spring 1843;Chang et al 2012), Myanmar (Chang et al 2012;Parveen et al 2017), Peninsular Malaysia and Singapore (Turner et al 1998;Chua et al 2005;Bedawi et al 2009), Philippines (Alston 1935;Zamora et al 1999;Tan 2013;De Guzman et al 2014), Sumatra (Sauerborn 2003;Beukema and Noordwijk 2004), Borneo (Said 2005;Ahmad and Holdsworth 2008;Komara et al 2016), Sulawesi (Mansur 2003; Hidayat 2011), Java (Rahayu et al 2012;Setyawan et al 2013;Setyawan et al 2015a;b;Setyawan et al 2016;Trimanto and Hapsari 2016), and Papua (Sambas et al 2003;Ebihara et al 2012;Johns et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Among cancers, the most common types are breast cancer, lung cancer, colorectal cancer, prostate cancer, skin, and stomach cancer. The ongoing conventional chemotherapies, radiotherapy treatment, and surgeries have shown a large number of involuntary side effects due to insufficient knowledge of treatment specificity, and are not recommended for long-term usage [ 105 , 106 ].…”
Section: Leo Therapeuticsmentioning
confidence: 99%